A alienação do trabalho docente na Rede Municipal de Ensino de Goiânia - Carmo, Renato Regis do (2017)
This work is the result of master’s dissertation submitted to the Graduate Program in Education of the Federal University of Goiás, which aimed to investigate the alienation present in the teaching work of the Municipal Goiânia Education (RME). The starting point was the work of alienation conceptions formulated by Marx and Marxist authors to understand how the social relations of capitalist production limit the possibilities of full realization of the human being. The advance of capital in sectors previously considered unproductive, as public school, imposes the need for the organization of work according to the current regulations, involving the linking of teaching activity to the production and realization circuit of surplus value. In the field research, we tried to outline how the alienation process takes place and the way that teachers understand it.